Integration of biological and chemical control of the whitefly Trialeurodes vaporariorum (Hemiptera: Aleyrodidae) - LÓPEZ, SILVIA N.; RIQUELME, MARÍA B.; BOTTO, EDUARDO (Revista Colombiana de Entomología, 2010)
Trialeurodes vaporariorum is an important pest associated with tomato crops, whose control is based on the use of agrochemicals. The objective of this work was to evaluate the integration of chemical and biological control of T. vaporariorum through the use of the parasitoid Encarsia formosa (Hymenoptera: Aphelinidae) (CBCQ), and to compare this management strategy to one based on the exclusive use of insecticide applications (CQ). Experiments were carried out in experimental greenhouses between August and December, 2005. Twelve plants per greenhouse were examined weekly, recording the number of adults on the two upper leaves and the number of normal and parasitized fourth instar nymphs on a leaflet of the middle third of the plant. The action threshold to conduct chemical control treatments in all greenhouses was the recording of  8 nymphs on average per leaflet, and to release the parasitoid in the CB-CQ treatment it was  1 nymph per greenhouse. Three peaks of adults and two peaks of nymphs were observed, surpassing the action threshold for application of agrochemicals. In treatment CQ, five insecticide applications were made, while in treatment CB-CQ eight releases of E. formosa and two applications with a product less harmful to the parasitoid were made. Parasitism by E. formosa in treatment CQCB reached 75% toward the end of the study. The results indicate that the use of this parasitoid can contribute to control of the pest, decreasing the number of insecticide applications.